Database of protein sequence alignments: PIR-ALN. - Srinivasarao, G Y (1999)
The Protein Information Resource (PIR) has been maintaining a database of curated protein sequence alignments since 1991. The collection includes superfamily, family and homology domain alignments. CLUSTAL V/W is used to generate multiple sequence alignments and ALNED, an interactive alignment editor, is used to check and correct them. The database has helped in classifying sequences, in defining new homology domains, and in spreading and standardizing protein names, features and keywords among members of a family or superfamily. The ATLAS information retrieval system can be used to browse and query the PIR-ALN alignments. The quarterly and weekly updates can be accessed via the WWW at http://www-nbrf. georgetown.edu/pir/